A study on microfluidic desalination using short chain fatty acid by directional solvent extraction in a serpentine micromixer. - Teo, Alvin H. H.; Chin, Sim Yee; Ling, Fiona W. M.; Abdulbari, Hayder A. (Taylor & Francis, 2025)
Water shortage is an imminent issue in the foreseeable future while thermal desalination techniques are energy intensive. This study investigates a membrane-less low temperature technique known as directional solvent extraction (DSE) desalination in a serpentine microchannel at 45, 50, 55, 60 and 65 deg. C. Two lower fatty acids, heptanoic acid (HeptA) and nonanoic acid (NonA) were used as the solvents to recover water from a 35000 ppm total dissolved solids (TDS) seawater at 2, 3, 4 and 5 organic to aqueous flowrate ratios (O: aq). Custom-made polydimethylsiloxane (PDMS) – glass microfluidic device is fabricated via direct writing lithography with depth and length of 100 mm and 161 mm respectively while the width is varied from 400 - 800 mm. Droplets were generated during the extraction process to maximize diffusion by using a 90 deg. T-junction where the organic solvent is the continuous phase and seawater is the dispersed phase. A maximum product water yield, Yw of 4 % v/v and 1.9 % v/v is achieved by HeptA and NonA respectively. The product water recovered from HeptA and NonA has salinity as low as 0.01% and 0.08%, respectively. The HeptA system produces water containing higher solvent residuals than the NonA system. HeptA is a better solvent as it can extract approximately two times more water than NonA under the same operating conditions. Both solvents are reusable.